ASSESSING THE IMPACT OF DIFFERENTIATED INSTRUCTION ON ENHANCING STUDENTS’ SPEAKING PROFICIENCY - Nurelviani, Destia; Prastyo, Yanuar Dwi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
The primary goal is to assess how differentiated instruction influences students' fluency, pronunciation, and vocabulary acquisition in English. The research employs a quasi-experimental one-group pretest-posttest design, involving 13 eleventh-grade students selected through purposive sampling, focusing on those with initial difficulties in speaking. The study progresses through three stages: initial observation and pre-test, structured differentiated instruction intervention sessions, and a post-test to measure improvements. Findings show a significant improve ment in speaking skills, with a mean difference of 2.48 between pretest and posttest scores, supported by a p-value of 0.00, indicating the effectiveness of differentiated instruction. The greatest improvement was observed in vocabulary, followed by comprehension and gram mar. Despite the study's limitations, such as a small sample size and lack of a control group, the results underscore the potential of differentiated instruction as a valuable teaching strategy for addressing individual learning needs. These findings suggest that differentiated instruction can be an effective approach for enhancing English language proficiency in diverse classroom settings.